Management of industrial service projects developed by Brazilian companies and their relationship with critical success factors - Machado, Isabelle Confort; Rampasso, Izabela Simon; Quelhas, Osvaldo Luiz Gonçalves; Leal Filho, Walter; Minatogawa, Vinicius Luiz Ferraz; Franco, Matheus Munhoz Vieira; Anholon, Rosley (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose – This study aims to analyze the project management of industrial services developed by Brazilian companies and their relationship with Critical Success Factors. Theoretical framework – Through a content analysis, Critical Success Factors were aligned to industrial service management and PMBOK project management guidelines. Design/methodology/approach – To develop the study, a survey on industrial service project management was carried out on industrial service professionals. Survey data were analyzed through frequency distribution and ranked using the TOPSIS technique. Findings – The results showed that the companies mentioned use PMBOK guidelines, however, they can be improved. Comparatively, the project schedule management is highlighted; the five CSFs that are considered more relevant are related to the scope, schedule, costs, integration, communications and resource management. Research, Practical & Social implications – The results provide insights for organizational practices and guide management improvements, showing the main opportunities for improvement in the companies analyzed. Originality/value – The literature fails to provide an analysis of Brazilian industrial service companies. In this sense, this study provides a valuable contribution to the field. Keywords: Industrial Services Management; Critical Success Factors; Project Management; Brazil.